Proposal of initiative service model for service robot. Issue 4 (26th April 2019) - Hao, Man; Cao, Weihua; Wu, Min; Liu, Zhentao; She, Jinhua; Chen, Luefeng; Zhang, Ri
Abstract : Service robots are becoming a part of today's life. To realise friendly human–robot interaction, an initiative service model for service robot is proposed, which is composed of three layers, i.e. information acquisition layer, in which communication information and environmental information are collected by sensors; decision layer, in which personal intention and emotional states are obtained by multi‐modal emotion recognition and intention understanding, and users' demands are obtained by demand analysis model; initiative service execution layer, in which the task execution and emotion adaption of robot are carried out. Initiative service can sense motive of people, by which a humanised and real‐time service could be realised. Drinking service experiments are performed, including passive service and initiative service of robots. Experimental results show that the drinking time of passive service lags behind the initiative service 30 min on average, and the initiative service renders drinking service 2 times more than passive service on average, besides, the water quantity provided by initiative service is more reasonable, which demonstrates the feasibility of the proposal. In prospect, initiative service model could be applied to many occasions in people's daily life, e.g. family service, caring for the elderly, and medical rehabilitation.